2022
DOI: 10.3390/diagnostics12061461
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Values of Peptidoglycan, Lipopolysaccharide, and (1,3)-Beta-D-Glucan in Patients with Suspected Bloodstream Infection: A Single Center, Prospective Study

Abstract: This study aimed to assess the diagnostic values of peptidoglycan (PGN), lipopolysaccharide (LPS) and (1,3)-Beta-D-Glucan (BDG) in patients with suspected bloodstream infection. We collected 493 heparin anticoagulant samples from patients undergoing blood culture in Peking Union Medical College Hospital from November 2020 to March 2021. The PGN, LPS, and BDG in the plasma were detected using an automatic enzyme labeling analyzer, GLP-F300. The diagnostic efficacy for PGN, LPS, and BDG were assessed by calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…It was reported that serum LPS is effective in the early detection of bloodstream infections caused by Gram-negative bacteria. 40 After daubing with different bacterial concentrations, serum LPS levels were increased in all infected groups (10 7 CFU/mL, 10 8 CFU/mL and 10 9 CFU/mL), compared with control and sham groups. LPS as a component of Gram-negative bacteria’s cell wall can activate inflammatory cells and factors in tissue, resulting in severe pathophysiological symptoms like sepsis, or multiple organ failure.…”
Section: Discussionmentioning
confidence: 85%
“…It was reported that serum LPS is effective in the early detection of bloodstream infections caused by Gram-negative bacteria. 40 After daubing with different bacterial concentrations, serum LPS levels were increased in all infected groups (10 7 CFU/mL, 10 8 CFU/mL and 10 9 CFU/mL), compared with control and sham groups. LPS as a component of Gram-negative bacteria’s cell wall can activate inflammatory cells and factors in tissue, resulting in severe pathophysiological symptoms like sepsis, or multiple organ failure.…”
Section: Discussionmentioning
confidence: 85%